Static load sharing performance of non-orthogonal and offset helical face gear dual-branch drivetrain - Xuezhong Fu; Chunyu Zhang; Haijun Xu; Yingqiang Xu; Guo Ma; Houbing He (Advances in Mechanical Engineering)
To research the static load sharing performance of non-orthogonal offset helical (NOH) face gear dual-branch drivetrain, the non-orthogonal offset layout forms of the system are explored, and the meshing phase differences of split-stage and converge-stage are analyzed. Based on the torque balance condition, deformation coordination condition, and static balance condition of the system, a static torque distribution model of the system was generated, and the static load sharing coefficients (SLSCs) were obtained results. The influence of assembly errors, support stiffness, torsional stiffness, meshing stiffness, and input load on the static load sharing performance was analyzed. The results indicate that assembly errors have a strong influence on the SLSCs, with the shaft angle errors exerting the strongest influence on the SLSCs; When there are assembly errors, the impact of input load and torsional stiffness on the static load sharing performance is greater than without assembly error. To increase the load sharing performance of the system, the meshing phase differences should be eliminated, and the offset layout form should be adopted in the dual-branch transmission system. In addition, reducing the support stiffness of the input helical gear and the fluctuation amplitude of meshing stiffness can also improve the load sharing performance.